Implementing CEFR in secondary education: impact on FL teachers' educational and assessment practice. (15th January 2013) - Moonen, Machteld; Stoutjesdijk, Evelien; de, Rick; Corda, Alessandra
<x xml:space="preserve">Abstract</x> In order to study the impact of the Common European Framework of Reference for Languages (CEFR) on foreign language teachers' teaching and assessment practice, a survey, interviews and case studies were carried out in Dutch secondary education. Teachers' perceptions, their needs and plans, and the implementation of CEFR were studied. Results show that the use of CEFR is most widespread in the use of CEFR‐related textbooks. The group of teachers that apply CEFR more extensively is relatively small. Schools differ considerably with respect to the application of CEFR for curriculum planning and for assessment and professional development. These results are discussed in the light of factors that foster the implementation of educational innovations, such as compatibility and adaptation at school and teacher level.